Anaplastic multiple myeloma with MYC rearrangement. (2022) - Ichikawa, Satoshi; Fukuhara, Noriko; Hashimoto, Ko; Fujishima, Fumiyoshi; Ichinohasama, Ryo; Harigae, Hideo
Abstract: A 52-year-old man with rapidly progressive paraplegia was presented to us with paravertebral tumors. Laminectomy with tumor resection was performed, and pathological analysis of the tumor revealed compact proliferation of anaplastic plasmacytoid cells. G-band analysis of the tumor revealed a complex karyotype, including IgH/MYC translocation. The patient was diagnosed with anaplastic multiple myeloma (AMM) with MYC arrangement, and cytotoxic chemotherapy followed by autologous hematopoietic stem cell transplantation resulted in long-term disease-free remission. This is the first report describing a case of de novo AMM with MYC rearrangement, suggesting that conventional chemotherapy could be a treatment option for this formidable disease.